Learning styles: determinants in achieving english proficiency / Nadirah Abd Latiff and Nurul Syazwani Mohd Kamil - Abd Latiff, Nadirah; Mohd Kamil, Nurul Syazwani (2018)
Communication is an important aspect in everyday activities. In universities, students are imparted with the knowledge of learning either a second language or third language for them to be able to communicate with each other. English, selected as the language most understood by different nations is a must-learned language. However, there are difficulties in learning another language besides your mother tongue. Therefore, exists learning styles as aids in helping one understand their learning styles and further improve their learning in said subject; English. With that, the present study examines the students’ learning styles in achieving English proficiency in UiTM Terengganu. The Honey and Mumford’s learning styles questionnaire consists of four aspects; activist, reflector, theorist and pragmatist. The participants for this study are hospitality degree students of UiTM Terengganu Campus Dungun; the Bachelor in Sc. of Hotel Management (HM240) and Bachelor in Sc. of Food & Beverage Service (HM242) students. The study reports the results obtained from the study as well as the recommendations for future study.